Kreativitas Ramah Lingkungan dalam Bingkai Pariwisata Budaya: Pelatihan Pembuatan Kursi Sofa dari Botol Plastik Bekas di Sanggar Budaya Mawarane Nita - Paulus Nong Wisang; Natalia Kristiani Tandafatu; Leonardus Winarto (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
The problem of plastic waste is a serious challenge in tourism development, including in the development of culture-based tourism. The low level of plastic waste recycling at the community level demonstrates the need for an educational approach that is applicable and empowering. The Community Service Program (PKM), conducted by a team of lecturers and students from the Ecotourism study program at Cristo Re Polytechnic, aims to increase ecological awareness and creative skills among members of the Mawarane Cultural Studio, through training in making sofa chairs from used plastic bottles. The methods used included participatory counseling, demonstrations, hands-on practice, and mentoring over three days. The results of the activity showed an increase in participants' understanding of the concepts of the circular economy and waste management, as well as technical skills in producing simple furniture products that are functional and aesthetically valuable. In addition to producing a physical output in the form of a sofa prototype, the program also encouraged a collective commitment to developing environmentally friendly creativity as part of the studio's identity. This activity demonstrates that the integration of cultural preservation, community empowerment, and environmental management can be an innovative model in supporting sustainable, community-based tourism.